Customer Trust and Profit Sharing Transparency in Enhancing Mudharabah Contract Growth - Intan Suwandi; Salman Nasution (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2026)
This study investigates the influence of customer trust and profit-sharing system transparency on the growth of mudharabah contracts in Islamic banking. The research was motivated by fluctuations in customer participation and concerns regarding the clarity of profit-sharing mechanisms. Using a quantitative survey approach, data were collected from 100 customers through structured questionnaires. Instrument validity and reliability were tested, followed by classical assumption checks and multiple linear regression analysis to examine both partial and simultaneous effects of the independent variables. The findings reveal that customer trust (X1) significantly and positively affects the number of mudharabah contracts (Y), indicating that integrity and professional service strengthen confidence in sharia-compliant products. Likewise, transparency of the profit-sharing system (X2) exerts a significant influence, as accessible and clear reporting reduces uncertainty (gharar) and enhances customer security. Simultaneously, the synergy between trust and transparency accelerates contract growth. These results imply that strengthening transparency and customer trust is essential for sustainable mudharabah development. Practically, the study contributes to advancing Islamic financial literacy and reinforcing public confidence in mudharabah as a transparent, fair, and sharia-compliant financing instrument.